A High‐Energy Density Li‐Ion Hybrid Capacitor Fabricated from Bio‐Waste Derived Carbon Nanosheets Cathode and Graphite Anode (Global Challenges 10/2022). Issue 10 (19th October 2022) - Nanaji, Katchala; Pappu, Samhita; Anandan, Srinivasan; Rao, Tata N.
Abstract : In article 2200082, Katchala Nanaji, Tata N. Rao, and co‐workers, demonstrate a unique, cost‐effective strategy to develop high‐surface‐area porous carbon nanosheets from bio‐waste to be employed as a potential cathode for a Li‐ion capacitor, achieving both high energy and power density in a single energy storage system.